Political Ethics Education and Student Political Culture: Legal Awareness as a Predictor of Democratic Participation among University Students - Saryono Saryono; Sunarso Sunarso; Nasiwan Nasiwan (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study aims to examine the relationship between political ethics education and legal awareness on students’ political culture within the context of university organizations. A correlational quantitative design with a cross-sectional approach was employed. The participants consisted of 30 undergraduate students actively involved in campus organizations, selected through purposive sampling. Data were collected using a four-point Likert-scale questionnaire that met validity and reliability requirements (α = 0.79–0.85). Multiple regression analysis was conducted after fulfilling classical assumptions. The results indicate that political ethics education has a positive and significant effect on students’ political culture (β = 0.621; p < 0.01), as does legal awareness (β = 0.412; p < 0.05). Simultaneously, both variables explain 85.5% of the variance in political culture (R² = 0.855; p < 0.001). These findings suggest that the internalization of political ethics and legal understanding plays a crucial role in shaping students’ democratic participation. However, the results should be interpreted cautiously due to the limited sample size and non-random sampling.